2019
DOI: 10.4097/kja.d.18.00290
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal nebulization versus intraperitoneal instillation of ropivacaine for postoperative pain management following laparoscopic donor nephrectomy

Abstract: Background: Laparoscopic donor nephrectomy is considered less painful than open nephrectomy but is still associated with significant postoperative pain. Studies reported that intraperitoneal instillation of local anesthetics provides uncertain pain relief after laparoscopic surgery. This randomized, double-blind study evaluated the effect of intraperitoneal nebulization of ropivacaine on postoperative pain relief after laparoscopic donor nephrectomy. Methods: Sixty patients undergoing elective laparoscopic don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…However, pectoral pain was controlled better in group P (PEC II), and shoulder pain was significantly less in group S (intergroup P < 0.05 at 12 h). Static pain is described as pain at rest, whereas dynamic pain is defined as pain on deep breathing, coughing or movement [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pectoral pain was controlled better in group P (PEC II), and shoulder pain was significantly less in group S (intergroup P < 0.05 at 12 h). Static pain is described as pain at rest, whereas dynamic pain is defined as pain on deep breathing, coughing or movement [11].…”
Section: Discussionmentioning
confidence: 99%
“…The arm on the same side as the operation was positioned at 90° abduction, and the area of the block was painted using betadine with alcohol. The ultraso-nography (USG) machine was prepared using a linear transducer (6)(7)(8)(9)(10)(11)(12)(13), and the probe was covered with a sterile sheet. Intraoperatively, all patients received paracetamol 1 gm intravenous (i.v) before the start of the surgical incision and an injection of fentanyl 1 μg/kg/h till completion of surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Since a homogeneous IP distribution of viscous materials such as hydrogels cannot be obtained with the nozzle currently used in (e)­PIPAC surgeries, a novel nozzle was developed in collaboration with Medspray. In a preclinical setting, other research groups have developed a variety of alternative nozzle designs, based on the same nebulization mechanism as the Capnopen, i.e., high pressure atomization, , and different aerosolization principles, such as jet nebulization, , mesh nebulization, and ultrasonic nebulization, , with the aim to improve the uniformity of the IP aerosol deposition of non-viscous aqueous solutions . The majority of these investigational nozzles aim to produce aerosols with a reduced droplet size because the distribution of smaller aerosol droplets is assumed to be less influenced by gravity.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Catenacci et al, [ 15 ] intraperitoneal nebulization and peritoneal instillation of ropivacaine were compared and nebulization was found to be superior to instillation of ropivacaine. Somaini et al [ 16 ] and Kumar et al [ 17 ] studied the effects of peritoneal ropivacaine nebulization in laparoscopic gynecologic surgery and donor nephrectomy, respectively, and found it to be effective in reducing postoperative pain, which resulted in early ambulation and discharge. Das et al [ 18 ] used intraperitoneal nebulization of ropivacaine and found that it reduced pain scores in the early postoperative period making laparoscopic cholecystectomy more amenable to day care surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] Bhatia et al [ 6 ] used ingeniously prepared nebulization kit made from the ordinary nebulizer and silicon tubing and achieved adequate analgesia when ropivacaine along with fentanyl was used for intraperitoneal nebulization. Kumar et al[ 22 ] in their study on donor nephrectomy found that intraperitoneal instillation of ropivacaine reduced postoperative pain. Porika et al[ 23 ] compared intraperitoneal nebulizations of ropivacaine and bupivacaine and observed that both were equally efficacious in reducing pain.…”
Section: Discussionmentioning
confidence: 99%